Analysis of the efficiency of slow filtration for the water treatment of a born situated in the rural area of Passabém – MG (Research, Society and Development, 2018)
Residents of rural communities do not always have access to treated water, culminating in the use of water of doubtful quality. Thus, in order to improve the quality of water from a source used for supply at Fazenda Córrego dos Pinheiros, located in the rural area of Passabém (MG), this work aims to evaluate the efficiency of a slow filtration system for the removal of total solids, turbidity and Escherichia coli (E. coli). In addition, satellite images analyzed the use and occupation of the soil in this region in the last ten years and the neighbors’ perception about the water quality consumed by them. Data were collected through experimental research, laboratory research, documentary analysis and questionnaires, which were treated through descriptive statistics and content analysis. Thus, in the last 10 years, there was a small regeneration in an area of forest preserved in the vicinity of the farm, in addition, there was no increase in the number of buildings in the surroundings. Among the parameters that were analyzed, the slow filter proved to be efficient for the treatment of water, since with respect to E. coli, for example, a 100% removal efficiency was observed. However, it is noteworthy that the verified results regarding turbidity, total solids and pH parameters were already in compliance with Ministry of Health Ordinance nº 2.914/2011 before being submitted to the slow filter treatment. Although all residents claim to use spring water, most of them did not do any treatment before. It can be seen that, in general, for the residents participating in this research, apparently clean water is a sufficient characteristic to guarantee their quality for consumption.